Genealogy and Critique in Kant’s Organic History of Reason - Jennifer Mensch (Con-textos Kantianos: International Journal of Philosophy, 2015)
Although scholarly attention has been mostly paid to the many connections existing between Kant and the exact sciences, the landscape of Kant studies has begun to noticeably change during the last decade, with many new pieces devoted to a consideration of Kant’s relation to the life sciences of his day. It is in this vein, for example, that investigators have begun to discuss the importance of Kant’s essays on race for the development of Anthropology as an emerging field. The bulk of the contributions to this recent trend, however, have focused on Kant’s remarks on organic life in the Critique of Judgment, such that Kant’s “theory of biology” is now seen to be firmly located in that text. Amidst such consolidation, there are a few pieces that have begun to address Kant’s appeal to organic vocabulary within the context of his theory of cognition, though these too remain dominated by the interpretive template set by the third Critique. My own strategy in this essay will be different. Kant did indeed borrow from the life sciences for his model of the mind, but in a manner that would reject a naturalized account. His preference for epigenesis as a theory of organic generation needs to be carefully distinguished, therefore, from the use he would make of it when discussing a metaphysical portrait of reason.